Heterosis and Combining Ability Estimates using Line x Tester Analysis to Develop Rice Hybrids for Temperate Conditions - Gulzar S. SANGHERA; Waseem HUSSAIN (Notulae Scientia Biologicae, 2012)
Heterosis and combining ability estimates were worked out through Line x Tester analysis of 36 hybrids developed by crossing 18 lines (Males) with two cytoplasmic male sterile (CMS) lines (Females) to know the genetic architecture of various agro-morphological traits in rice for development of hybrids under temperate conditions. Analysis of variance revealed significant differences among genotypes, crosses, lines, testers and line x tester interactions for all the studied traits. Preponderance of non-additive gene effects was realized by higher values of specific combining ability compared to general combining ability, ratio of variances of SCA to GCA and average degree of dominance. The proportional contribution of testers was observed to be lower than that of line x tester interactions thus higher estimates of SCA variances. The estimates of GCA effects indicated male parent K-08-61-2 was good general combiner for grain yield per plant and other yield contributing traits and among the female parent SKAU 11A was observed to be good general combiner. Cross combinations SKAU 7A x K-08-61-2, SKAU 7A x SR-2, SKAU 11A x K-08-60-2, SKAU 11A x K-08-59-3 and SKAU 11A x SKAU-389 were found to be good specific combinations for grain yield per plant and other desirable traits and needs to be tested on large scale.